Cardiotoxicity of Epidermal Growth Factor Receptor 2-Targeted Drugs for Breast Cancer - Yang, ZiYan; Wang, Wei; Wang, Xiaojia; Qin, ZhiQuan (Frontiers in Pharmacology, 2021)
Breast cancer is the most common tumor in women, and its number is increasing year over year. Human epidermal growth factor receptor 2 (HER2 or ErbB2) overexpression is responsible for 20% to 25% of invasive breast cancers and is associated with poor prognosis. HER2 therapy has significantly improved overall survival in patients with HER2(+) breast cancer. However, despite its therapeutic benefits, its cardiotoxicity is a major concern, especially when used in conjunction with anthracyclines. The main anti-ErbB2-targeting drugs with cardiotoxicity are the mechanism of cardiotoxicity induced by drugs is not fully understood. Currently, NGR1 / HER-2 inhibiting HER dimer formation causes increasing ROS in mitochondria, and inhibition of PI3K/Akt and Ras/MAPK pathways directly leads to cell apoptosis. MMP2 are newly discovered pathways. In addition, although ACEIs /ARBs/β-blockers and other drugs have an inhibitory effect on heart dysfunction caused by ErbB2-targeted drugs. NT-proBNP does well in monitored TIC during target drugs treatment and a predictive effect on disease prognosis. It is non-invasive, inexpensive, reproducible, and worthy of the attention of clinicians. NT-proBNP may serve as a biological marker for clinical prediction of the occurrence of cardiotoxicity.